Epigrafi Islam: Telusuran Sejak Orde Baru Hingga Kini - Tawalinuddin Haris (Jurnal Lektur Keagamaan, 2014)
Studies in Islamic Epigraphy in Indonesia had been conducted by many national and international experts. This study focus on researchs of incriptions  that have not yet reviewed or the researchs that correcting/criticize the previous research. The study limited to research discussion about  Islamic inscription in Indonesia since the new order era until  the beginning of the 21st century. This effort  has be  done as assessments to furnish the report that has been done by  Uka Tjandrasasmita in articles investigation  the acts of paleontologists Islam in Indonesia.  This research concluded that there are many uniqueness that was found in Indonesian Islamic inscription  that the possibility of not there are in other countries.Keywords: Epigraphy, Puslitarkenas